Minimal Aortic Injury Detected on Computed Tomography Angiography during Initial Trauma Imaging: Single Academic Level 1 Trauma Center Experience - Gharai, Leila Rezai; Ovanez, Christopher; Goodman, William C.; Deng, Xiaoyan; Bandyopadhyay, Dipankar; Aboutanos, Michel B.; Parker, Mark S. (AORTA, 2022)
Background Minimal aortic injury (MAI), a subtype of acute traumatic aortic injury, is being increasingly recognized with better imaging techniques. Given conservative management, the role of follow-up imaging albeit important yet has to be defined.Methods All trauma chest computed tomography angiographies (CTAs) at our center between January 2012 and January 2019 were retrospectively reviewed for presence of MAI. MAIs were generally reimaged at 24 to 72 hours and then at a 7- and 30-day interval. Follow-up CTAs were reviewed for stability, progression, or resolution of MAI, along with assessment of injury severity scores (ISS) and concomitant injuries, respectively.Results A total of 17,569 chest CTAs were performed over this period. Incidence of MAI on the initial chest CTA was 113 (0.65%), with 105 patients receiving follow-up CTAs. The first, second, third, and fourth follow-up CTAs were performed at a median of 2, 10, 28, and 261 days, respectively. Forty five (42.9%), 22 (21%), 5 (4.8%), and 1 (1%) of the MAIs were resolved by first, second, third, and fourth follow-up CTAs. Altogether, 21 patients showed stability (mean ISS of 16.6), and 11 demonstrated improvement (mean ISS 25.8) of MAIs. Eight patients had no follow-up CTA (mean ISS 21). No progression to higher-grade injury was observed. Advancing age decreased the odds of MAI resolution on follow-up. A possible trend (p-value 0.22) between increasing ISS and time to resolution of MAIs was noted.Conclusion In our series of acute traumatic MAIs diagnosed on CTA imaging, there was no progression of injuries with conservative management, questioning the necessity of sequential follow-up imaging.
Keywords: minimal aortic injury; CT angiography; blunt thoracic aortic injuries